Strategy for Reinforcing Students’ Integrity Values through Exemplary and Advice Methods of Darul Ulum Muhammadiyah Islamic Boarding Schools, Kulon Progo - Rudiyanto Rudiyanto; Khoiruddin Bashori; Muhammad Samsudin (International Journal of Social Service and Research, 2022)
Ahlakul karimah (divine character) is the primary criterion for observing and evaluating the outward nature of a person, but various traits and characteristics of children cannot be separated from the influence of their parents or elders. In addition to being required to maintain their children's educational development, parents must be able to recognize and cultivate their children's potential and must not impose their will without first consulting them. Nonetheless, in the contemporary era, education faces increasingly complex obstacles, particularly as the world of online media devices becomes more accessible to the public. In order for a child to realize good morals, he or she must have a model to follow, and educational institutions are the key. This study aims to examine the position of Islamic boarding schools, which are prevalent in Indonesia, particularly on the island of Java, in relation to the level of students' honesty using a method based on emulation and advice from boarding school administrators. The method of this research is a descriptive-analytic qualitative research with a case study approach. The results of study show that the exemplary method in strengthening the values of honesty at the Darul Ulum Muhammadiyah Galur Islamic Boarding School includes two forms of the first method, namely directly through the words and behavior of the management and the second, which indirectly means through stories influence students’ characteristics.